1998
DOI: 10.1074/jbc.273.24.14885
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Endothelial Nitric-oxide Synthase by Lysophosphatidylcholine

Abstract: We have shown that lysophosphatidylcholine (lyso-PC) increases endothelial nitric-oxide synthase (eNOS) expression at the transcriptional level (Zembowicz, A., Tang, J.-L., and Wu, K. K. (1995) J. Biol. Chem. 270, 17006 -17010). To elucidate the mechanism by which lyso-PC increases the eNOS transcription, we identified Sp1 sites at ؊104 to ؊90 and PEA3 sites at ؊40 to ؊24 as being involved in lyso-PC-induced promoter activity. Site-directed mutagenesis of Sp1 sites resulted in a marked reduction of basal and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 33 publications
2
68
0
1
Order By: Relevance
“…The association of decreases in Sp1 binding with promoter activation at first seemed paradoxical. However, other investigators have shown that, in contrast to its accepted role as a homeostatic transactivator (14,15), Sp1 binding can sometimes function as a gene repressor (16,17). Our results demonstrate that the proximal Sp1 binding site in the TNF-␣ promoter can function as a repressor element.…”
Section: Functional Analysis Of Sp1 Binding Sites In a Heterologousmentioning
confidence: 44%
See 1 more Smart Citation
“…The association of decreases in Sp1 binding with promoter activation at first seemed paradoxical. However, other investigators have shown that, in contrast to its accepted role as a homeostatic transactivator (14,15), Sp1 binding can sometimes function as a gene repressor (16,17). Our results demonstrate that the proximal Sp1 binding site in the TNF-␣ promoter can function as a repressor element.…”
Section: Functional Analysis Of Sp1 Binding Sites In a Heterologousmentioning
confidence: 44%
“…Similar to CRE-binding proteins, cAMP-dependent protein kinase (PKA) phosphorylation of Sp1 has been shown to enhance its DNA binding activity (13). Although Sp1 binding can activate transcription (14,15), for some genes Sp1 functions as a repressor (16,17). The promoter motifs or cell characteristics that determine these divergent effects of Sp1 binding are not fully understood.…”
mentioning
confidence: 99%
“…Treatment of endothelial cells with lysoPC resulted in an increased transcription of the e-NOS mRNA in these cells, followed by an increased amount of protein and the corresponding activity. The time span needed for this response (33,34,18) in the case of injected saliva would preclude a significant role of lysoPC regarding the increase in local NO levels, because the feeding of R. prolixus is successfully accomplished in a few minutes (35). Perhaps in ticks, which remain attached to the host on the same site for a greater period, this role of lysoPC would be more noticeable.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Li et al (12) have reported that HDL binding to SR-BI activates eNOS in transfected Chinese hamster ovary (CHO) cells in an Akt-independent manner, possibly involving ceramide, whereas Mineo et al (13) reported that HDL caused eNOS activation through phosphorylation at Ser-1179 in both endothelial cells and COS M6 cells transfected with eNOS. Regulation of eNOS activity by phosphorylation is complex and involves an intricate interaction between multiple sites (Ser-116, Thr-497, Ser-617, Ser-635, and Ser-1179) and the activities of numerous kinases and phosphatases, including AMP activated protein kinase (AMPK) (14), PKA (15), Akt͞PKB (16), PKC (17), PP1 (18), and PP2A (19). In the current study, activation of eNOS was characterized by studying five phosphorylation sites within the eNOS enzyme.…”
mentioning
confidence: 99%